Comparative evaluation of apical extrusion of debris and irrigant with three rotary instruments using crown down technique – An in vitro study - Rahul Jindal; Smita Singh; Siddharth Gupta; Punita Jindal (Journal of Oral Biology and Craniofacial Research)
Aims and objective: The purpose of this study was to evaluate and compare the apical extrusion of debris and irrigant using various rotary instruments with crown down technique in the instrumentation of root canals. Material and Method: Thirty freshly extracted human permanent straight rooted mandibular premolars with minimum root curvature of 0–10 ° were divided in three groups with 10 teeth in each group. Each group was instrumented using one of the three rotary instrumentation systems: Rotary Hero shapers, Rotary ProTaper and Rotary Mtwo. One ml of sterile water was used as an irrigant after using each instrument. Debris extruded was collected in pre weighed glass vials and the extruded irrigant was measured quantitatively by Myers and Montgomery method and was later evaporated. The weight of the dry extruded debris was calculated by comparing the pre and post instrumentation weight of glass vials for each group. Statistical analysis: Statistical analysis was done by using by a Kruskal–Wallis One-way ANOVA test. Results: Statistical analysis showed that all the rotary instruments used in this study caused apical extrusion of debris and irrigant. A Statistically significant difference was observed with Rotary ProTaper and Rotary Mtwo groups when compared with Rotary Hero shapers. But no significant difference was observed between Rotary ProTaper and Rotary Mtwo groups. Conclusion: After instrumentation with different rotary instruments, Hero shapers showed a less apical extrusion of debris and irrigant.